On civilization's edge : a Polish borderland in the interwar world - Ciancia, Kathryn (Oxford University Press, 2021)
In 1918, as Europe's continental empires were violently replaced with a patchwork of nominally post-imperial nation-states, elites in Poland drew on the global language of civilization to launch a state-building mission in the non-ethnically Polish, nationally contested, and war-torn region of Volhynia. By following eastward in the footsteps of border guards, military settlers, provincial administrators, regional activists, health professionals, urban planners, teachers, and academics, the work traces how a colorful cast of characters adapted the prevailing language of European imperialism while simultaneously rejecting the very idea that they could act imperialistically in an historically Polish borderland. Their tension-ridden approaches were never static. Some Polish nationalists declared that they alone could act as benign civilizational conduits in mainly Ukrainian villages and predominantly Jewish towns, while others attempted to craft a regional identity. But by the eve of the Second World War, the province had become a testing ground for visions of demographic transformation that favoured antisemitic schemes of Jewish emigration and the forced assimilation of non-Polish Slavs. Throughout, doubts about the national strength of local Poles, competitions between diverse groups of self-declared civilizers, and mounting anxieties about the rise of Nazi Germany and the Soviet Union, meant that Volhynia served as an arena for redefining the precise contours of the modern Polish nation. Rather than simply a successor state embroiled in the quintessentially east European problem of "national minorities," Poland was a place where people engaged with the concept of civilization, recasting its meaning in conceptual spaces between empire and nation-state.